Effects of Gibberellin and Melatonin Foliar Sprays on Basil Chemical Composition and Volatile Oil Yield under Water Stress - Khazal, Hala Faisal; Hanshal, Majid Ali (Journal of Tropical Crop Science, 2026)
This study investigated the potential of exogenous gibberellic acid (GA3) and melatonin (MT) to mitigate the adverse effects of drought stress on basil (Ocimum basilicum L.). Conducted in 2022 at the University of Baghdad, Iraq, the experiment employed a split-plot design within a completely randomized block design. Three irrigation intervals (3, 5, and 7 days) were assigned to the main plots, while subplots received a factorial combination of the plant growth regulator gibberellic acid (GA3; 0, 100, and 200 mg/L) and melatonin (0, 20, and 40 mg/L). Results indicated that moderate water stress with a 5-day irrigation interval significantly enhanced leaf nitrogen, phosphorus, and potassium nutrient content, total phenolic content, and volatile oil yield compared with the 3-day and 7-day irrigation intervals. The application of 200 mg/L GA3 and 40 mg/L melatonin consistently yielded the highest values for all physiological and chemical parameters. Significant double- and triple-interactions suggest that the synergistic application of GA3 and melatonin effectively improved basil secondary metabolism under water-limited conditions. These findings highlight a strategic approach for optimizing essential oil production in arid environments.